Aircraft Lateral-Directional Stability in Critical Cases via Lyapunov Exponent Criterion - Abdulwahab, Emad N.; Atiyah, Qasim A.; Abd Alzahra, Ali Talib (Al-Khwarizmi Engineering Journal, 2017)
Based on Lyapunov exponent criterion, the aircraft lateral-directional stability during critical flight cases is presented. A periodic motion or limit cycle oscillation isdisplayed. A candidate mechanism for the wing rock limit cycle is the inertia coupling between an unstable lateral-directional (Dutch roll) mode with stable longitudinal (short period) mode. The coupling mechanism is provided by the nonlinear interaction of motion related terms in the complete set equations of motion. To analyze the state variables of the system, the complete set of nonlinear equations of motion at different high angles of attack are solved. A novel analysis including the variation of roll angle as a function of angle of attack is proposed. Furthermore the variation of Lyapunov exponent parameter as function of time is introduced. The numerical result indicated that the system became lightly damped at high angle of attack with increasing the amplitude of aircraft state variables limit cycle. A good agreement between the numerical result and published work is obtained for the onset of limit cycle oscillation, almost at .